2012
DOI: 10.1161/circep.111.968008
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Arrhythmias Among Implantable Cardioverter-Defibrillator Recipients for Primary Prevention

Abstract: Background-An implantable cardioverter-defibrillator (ICD) is the therapy of choice for primary prevention in patients with ischemia who are at risk for sudden cardiac death (SCD). One third of patients with significant coronary disease have chronic total coronary occlusion (CTO), which is associated with long-term mortality in patients with previous myocardial infarction. However, the impact of CTO on the occurrence of ventricular arrhythmias and long-term mortality in ICD recipients remains unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 42 publications
6
81
0
6
Order By: Relevance
“…The current, substantially larger, study confirms this observation. Regarding appropriate device therapy, Nombela‐Franco et al found that patients with an ICD for ICM and a CTO experience more device therapy both in primary (n=162) and secondary (n=425) prevention 9, 10. We have also observed this in our cohort, suggesting that the presence of a CTO has more impact on the myocardium than 1 or more narrowed coronary arteries.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The current, substantially larger, study confirms this observation. Regarding appropriate device therapy, Nombela‐Franco et al found that patients with an ICD for ICM and a CTO experience more device therapy both in primary (n=162) and secondary (n=425) prevention 9, 10. We have also observed this in our cohort, suggesting that the presence of a CTO has more impact on the myocardium than 1 or more narrowed coronary arteries.…”
Section: Discussionsupporting
confidence: 74%
“…In Figure 4A and 4B, an overview of the available event rates for all‐cause death and appropriate device therapy of all studies on this subject is depicted 8, 9, 10. Event rates were numerically higher in CTO patients with an ICD for ICM, compared with patients without a CTO.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] Although better clinical outcomes have been associated with successful recanalization in observational studies, [6][7][8] CTO percutaneous coronary intervention (PCI) remains a major challenge for many interventional cardiologists, and developing new strategies to approach CTO is important for the field. Angiographic CTO lesion characteristics are predictive of success rate and procedure time.…”
mentioning
confidence: 99%
“…Among 162 patients with ischaemic cardiomyopathy who received an implantable cardioverter defibrillator, 44 % had at least one CTO. 44 During a median follow-up of 26 months, the presence of CTO was associated with higher ventricular arrhythmia and mortality rates (p<0.01). 44 The preventive effect of CTO revascularisation on subsequent arrhythmias remains to be shown.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 92%